Progress in Soybean Genetic Transformation Over the Last Decade - Xu, Hu; Guo, Yong; Qiu, Lijuan; Ran, Yidong (Frontiers in Plant Science, 2022)
Soybean is one of the important food, feed, and biofuel crops in the world. Soybean genome modification by genetic transformation has been carried out for trait improvement for more than 4 decades. However, compared to other major crops such as rice, soybean is still recalcitrant to genetic transformation, and transgenic soybean production has been hampered by limitations such as low transformation efficiency and genotype specificity, and prolonged and tedious protocols. The primary goal in soybean transformation over the last decade is to achieve high efficiency and genotype flexibility. Soybean transformation has been improved by modifying tissue culture conditions such as selection of explant types, adjustment of culture medium components and choice of selection reagents, as well as better understanding the transformation mechanisms of specific approaches such as Agrobacterium infection. Transgenesis-based breeding of soybean varieties with new traits is now possible by development of improved protocols. In this review, we summarize the developments in soybean genetic transformation to date, especially focusing on the progress made using Agrobacterium-mediated methods and biolistic methods over the past decade. We also discuss current challenges and future directions.